SIFAT MEKANIS KOMPOSIT BERPENGUAT BILAH BAMBU DENGAN MATRIKS POLYESTER AKIBAT VARIASI SUSUNAN - Wiwi Aprilia (PILLAR OF PHYSICS, 2013)
Research about composite mechanical from natural fiber expecially bamboo is still seldom used. Therefore, this research is done with purpose to know effect of piece arrangement of bamboo toward composites mechanic that include maximum tension value and elasticity  value. The research is experiment reseach. Piece of bamboo is arranged three variaties, are longer, across and plait. From three arrangement are counted tension value and elasticity to know mechanical characteristic. The results of this study: highest voltage value is 78.173 MPa in longer piece, tension value part of plait is shorter than longer piece 44.538 MPa and tension value of across fiber is shorter than embroidery piece 18.936 MPa. Result of measurement results to elasticity value in power curve the highest is 150.15 GPa in longer fiber, plait fiber is shorter than long fiber about 86.26 GPa and across fiber is shorter than plait about 50.209 GPa Keywords: bamboo, mechanical properties, composite, reinforcement, polyester